Reimagining Global Financial Settlements: A Gold-Backed Cryptocurrency Framework Anchored in Blockchain and Islamic Finance Principles - Irma Naddiya Binti Mushaddik (Al-Fadilah: Islamic Economics Journal, 2025)
In a world where economic turbulence and financial inequities are increasingly driven by the shortcomings of fiat currency systems, this paper advances a bold and timely proposition: the integration of gold-backed cryptocurrencies into global net settlement systems through blockchain technology. Bridging the philosophical depth of Islamic economic principles with the technical power of decentralized digital infrastructure, this study outlines a visionary framework that addresses the core weaknesses of inflation, centralization, and systemic risk. Grounded in qualitative research, including expert interviews and content analysis, the paper proposes a decentralized, ethically anchored, and technologically secure model that restores intrinsic value to money. Malaysia is identified as a strategic pioneer in this transformation, leveraging its leadership in Islamic finance and fintech to initiate a paradigm shift in global monetary governance. This work not only challenges existing financial orthodoxy but also provides a blueprint for a more stable, just, and transparent future of international finance